PEMERIKSAAN KADAR HB DAN PENYULUHAN TENTANG ANEMIA SERTA ANTISIPASINYA PADA SISWA SMA AL HIDAYAH - Hamimatus Zainiyah; Yogi Khoirul Abror (JURNAL PARADIGMA (PEMBERDAYAAN & PENGABDIAN KEPADA MASYARAKAT), 2019)
Anemia is a condition in which the components in the blood, namely hemoglobin (Hb) in the blood, are less than normal levels. Determination of anemia can also be done by measuring the hematocrit (Ht), which on average is equivalent to three times the hemoglobin level (Tarwoto, 2010). Based on the World Health Organization (WHO) 2010 states that of all adolescents in developing countries the prevalence of anemia in adolescent girls is 53.7%. The results of the Basic Health Research (RISKESDAS) in 2013, showed that the prevalence of anemia in Indonesia was 21.7%. Anemia patients aged 5-14 years were 26.4% and patients aged 15-24 years were 18.4% (Kemenkes RI, 2014). Based on a survey with interviews with 10 female students, 7 students experienced weakness, fatigue and lack of concentration on learning during menstruation and on physical examination showed pale conjunctiva. This is due to poor diet and insufficient iron intake. The method used to carry out community service is by conducting a preliminary study conducted at Al Hidayah High School, then conducting interviews about the understanding of anemia and how to anticipate it then making a time contract with students. The activity was continued with counseling and training in preparing a balanced menu, then continued with anamnese and examination of HB levels carried out at Al Hidayah High School. Of the 120 students, only 24 students showed signs and symptoms of anemia. Only students who showed signs and symptoms of anemia were tested for HB levels. While participating in the activities the students were very enthusiastic about the material presented, the students were also able to demonstrate compiling a balanced menu. The results of early detection of 24 students showed that 54.2% were not anemic and 45.8% had anemia.